PENGARUH MODEL PEMBELAJARAN EXPERIENTIAL LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI EKOSISTEM - Widiya Septian Dewi; Anita Restu Puji Raharjeng (Bioilmi: Jurnal Pendidikan, 2018)
Students' learning motivation in one of the high schools at Southern OKU is still categorized as low. Based on the results of observation and interview, the cause of low student learning motivation because the teacher does not use the learning model or teaching methods that exist in the teaching and learning process so that students feel bored and saturated. Based on these problems, this study aims to determine whether there is influence of learning model experiential learning on learning motivation. This research was conducted in May 2017. The research method used is experimental method with the research design used is quasi experimental design. Population in this study was all students of class X consisting of 3 classes there are X1, X2, X3 with the number of each class on average 37 students. Class X3 is as experiment class and X1 as control class. Sampling is done by purposive sampling technique. Data collection is using motivation questionnaire as primary data and observation of student learning motivation as secondary data. The results showed that H0 rejected Ha accepted so that the hypothesis states that experiential learning model influence on learning motivation.